EVALUASI PENGGUNAAN OBAT HIPERTENSI PADA PASIEN RAWAT JALAN DI RUMAH SAKIT BHAYANGKARA POLDA LAMPUNG TAHUN 2020 - Lilik Koernia Wahida; Novita Tri Wahyuni; Niluh Suastini (Program Studi Farmasi Universitas Tulang Bawang, 2023)
ABSTRACT Hypertension is a condition in which a person experiences an increase in blood pressure above normal, which is higher than 140 mmHg systolic or 90 mmHg diastolic. Hypertension plays a very important role in causing the death of thousands of people, due to its dangerous side-effects, such as stroke, heart attack, heart failure, and kidney failure. The purpose of this study is to evaluate the use of hypertension drugs in outpatient hypertension patients at Bhayangkara Polda Hospital Lampung. Evaluation of drug use is a quality assurance process in the use of drugs in hospitals aimed at ensuring the drugs used are appropriate, safe and effective. The data collection technique in this study began with the selection process of outpatient medical records who had a primary diagnosis of hypertension. The population in this study were all patient medical records at the Bhayangkara Polda Lampung Hospital in the period of 2020, the use of hypertension drugs based on the right patient was 103 patients, which was 100% correct, the use of Antihypertensive drugs based on the right indication was 103 patients, which was 100% correct. the use of antihypertensive drugs based on the right drug was 82 patients with a percentage (79.61%) of the right drug and as many as 21 patients (20.39%) the wrong drug because the drug given was not in accordance with the standard used, the use of antihypertensive drug was based on the right dose as much as 103 patients were 100% on the right dose, because the dose given was in accordance with the range of antihypertensive drug therapy based on JNC VIII. Keywords: hypertension, drug evaluation, drug use.